Immunohistochemical expression of B and T-lymphocytes and TGF-β in experimentally transplanted canine venereal tumor - Trompieri-Silveira, Ana Carolina [UNESP]; Gerardi, Daniel [UNESP]; Mouro, Juliana Vitti [UNESP]; Costa, Mirela Tinucci [UNESP]; Alessi, Antonio Carlos [UNESP] (FapUNIFESP (SciELO), 2009)
The tumor/host relationship may have a determining role in the progression or remission of a tumor. Greater infiltration of leukocytes into tumors has been associated with a better prognosis, although controversy regarding whether these cells have a central role in antitumor immunity still exists. Canine transmissible venereal tumor (TVT) is an experimentally transplantable type of tumor that has been used as an experimental model for the tumor/host relationship. The aim of this study was to evaluate the infiltration of T-lymphocytes (CD3, CD4, CD8) and B lymphocytes (CD79-α) and the expression of the cytokine TGF-β in TVT, by means of immunohistochemistry (ABC method). The experimental tumors were composed of puppies that developed TVT after transplantation, in the progression (n=8) (Group 1a), latency (n=8) (Group 1b) and regression (n=8) (Group 1c) phases of the tumor. CD3+T-lymphocytes predominated in the progression and regression phases, in relation to the latency phase. CD4+and 1CD8+ T-lymphocytes were predominant in the progression phase, and with lower expression in the regression phase. The greatest quantities of B-lymphocytes were in the regression phase, with restricted expression in the progression phase. TGF-β was expressed equally in the phases of the transplanted TVT.
Expressão imunoistoquímica de linfócitos T e B e do TGF-β no tumor venéreo transmissível canino experimentalmente transplantado
Keywords: Dog; Immunohistochemistry; Lymphocytes; TVT